A combined paleolimnological/genetic analysis of diatoms reveals divergent evolutionary lineages of Staurosira and Staurosirella (Bacillariophyta) in Siberian lake sediments along a latitudinal transect - Stoof-Leichsenring, Kathleen R. (Dr.); Bernhardt, Nadine; Pestryakova, Luidmila A. (Prof. Dr.); Epp, Laura Saskia; Herzschuh, Ulrike (Prof. Dr.); Tiedemann, Ralph (Prof. Dr.) (Journal of Paleolimnology, 2014)
Diatom diversity in lakes of northwest Yakutia (Siberia) was investigated by microscopic and genetic analysis of surface and cored lake sediments, to evaluate the use of sedimentary DNA for paleolimnological diatom studies and to identify obscure genetic diversity that cannot be detected by microscopic methods. Two short (76 and 73 bp) and one longer (577 bp) fragments of the ribulose 1,5-bisphosphate carboxylase/oxygenase (rbcL) gene, encoding the large subunit of the rbcL, were used as genetic markers. Diverse morphological assemblages of diatoms, dominated by small benthic fragilarioid taxa, were retrieved from the sediments of each lake. These minute fragilarioid taxa were examined by scanning electron microscopy, revealing diverse morphotypes in Staurosira and Staurosirella from the different lakes. Genetic analyses indicated a dominance of haplotypes that were assigned to fragilarioid taxa and less genetic diversity in other diatom taxa. The long rbcL_577 amplicon identified considerable diversification among haplotypes clustering within the Staurosira/Staurosirella genera, revealing 19 different haplotypes whose spatial distribution appears to be primarily related to the latitude of the lakes, which corresponds to a vegetation and climate gradient. Our rbcL markers are valuable tools for tracking differences between diatom lineages that are not visible in their morphologies. These markers revealed putatively high genetic diversity within the Staurosira/Staurosirella species complex, at a finer scale than is possible to resolve by microscopic determination. The rbcL markers may provide additional reliable information on the diversity of barely distinguishable minute benthic fragilarioids. Environmental sequencing may thus allow the tracking of spatial and temporal diversification in Siberian lakes, especially in the context of diatom responses to recent environmental changes, which remains a matter of controversy.